Pemaknaan Konten Youtube Fadil Jaidi Tentang Adab Kepada Orang Tua (Studi Resepsi pada Subscriber Millennial) - Wahdiyati, Dini; Ovita Violina, Kiki (CV. Publikasi Indonesia, 2023)
Youtube is indeed a substitution for a means of watching the content that can surpass television. The advantage of Youtube as a viewing medium is that it presents thematic shows that can be very closely related to the audience according to their respective interests. Thus the media of this era is very intimate with its users as well as its influence which will be more multiplying. This research examines the meaning of millennial viewers subscriber to Fadil Jaidi's Youtube channel who presents content in the form of witty activities and interactions by involving his father as a content attraction. Millennial subscribers as objects of warning were chosen because they are native viewers of Youtube media. The focus of this study looked at the audience meaning of the content of the episode